Accuracy of transvaginal and transrectal ultrasounds in the diagnosis of endometriosis: A retrospective cohort study - Zahra Asgari; Reihaneh Hosseini; Mahdi Sepidarkish; Azar Nabati (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Early diagnosis and appropriate treatment of endometriosis are vital and may prevent subsequent complications. Objective: To investigate the diagnostic accuracy of transvaginal ultrasound sonography (TVUS) and transrectal ultrasound sonography for detecting endometriosis considering the age and body mass index (BMI). Materials and Methods: This was a retrospective cohort study of 119 women scheduled for surgery in a tertiary health care center for clinically suspected endometriosis. Married and virgin women underwent TVUS and transrectal ultrasound sonography, respectively, before laparoscopic excision of endometriotic lesions. Results: The accuracy of TVUS in the diagnosis of right endometrioma in women with a normal BMI was superior to that in women with a BMI ≥ 30 (95.6% vs. 75.3%; p < 0.001). For the detection of left endometrioma in women with a normal BMI, TVUS demonstrated a sensitivity of 96.9% and a negative predictive value of 92.9%, which was significantly superior to TVUS in women with obesity (sensitivity: 77.4%, negative predictive value: 58.6%). The accuracy of TVUS in the diagnosis of left endometrioma in women under 35 yr was superior to that in women older than 35 yr (93.2% vs. 77.9%; p = 0.04). Similarly, the accuracy of TVUS in the diagnosis of right endometrioma in women under 35 yr was superior to TVUS in women older than 35 yr (86.5% vs. 73.3%; p = 0.04). Conclusion: Ultrasound can be a useful technique for detecting endometriosis when used adjunctively with the patient's history and physical findings, especially age and BMI.